1985
DOI: 10.1515/znb-1985-0901
|View full text |Cite
|
Sign up to set email alerts
|

Besetzungsvarianten der CaMnBi2-Struktur: Zur Kenntnis der Verbindungen LaZn0,52Sb2, LaCo0,68Sb2, LaMnxSb2 (0,65≤x≤ 0,76) und LaCux-Sb2 (0,82≤x≤ 0,87) / New Compounds with the CaMnBi2 Structure: On LaZn0,52Sb2, LaCo0,68Sb2, LaMnxSb2 (0,65≤x≤ 0,76) und LaCux-Sb2 (0,82≤x≤ 0,87)

Abstract: The new compounds LaZn0,52Sb2, LaCo0,68Sb2, LaMnxSb2 (0.65 ≤ x ≤ 0.76) and LaCuxSb2 (0.82 ≤x≤ 0.87) crystallize in the tetragonal system , space group P4/nmm (N o. 129) with the CaMnBi2 structure. The lattice constants are:LaZn0,52Sb2: a = 438.0(3) pm, c = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Single-crystal structure determinations of the antimonides CeAgSb (4, 10) and LaAuSb (6) showed that all atomic positions are fully occupied. In contrast, the structure refinements of three different crystals of the compound LaMn \V Sb showed considerable defects for the manganese position: LaMn Sb (11), LaMn Sb (6), and LaMn Sb (11). Similar defects were found during the structure refinements of LaCo Sb (11), LaCu Sb (11), LaCu Sb (11), LaZn Sb (11), and LaCd Sb (6).…”
Section: Introductionmentioning
confidence: 54%
“…Single-crystal structure determinations of the antimonides CeAgSb (4, 10) and LaAuSb (6) showed that all atomic positions are fully occupied. In contrast, the structure refinements of three different crystals of the compound LaMn \V Sb showed considerable defects for the manganese position: LaMn Sb (11), LaMn Sb (6), and LaMn Sb (11). Similar defects were found during the structure refinements of LaCo Sb (11), LaCu Sb (11), LaCu Sb (11), LaZn Sb (11), and LaCd Sb (6).…”
Section: Introductionmentioning
confidence: 54%
“…Linkage of the (still very hypothetical) one-dimensional XeO polymers (4) by sharing the remaining vertices will produce a two-dimensional square sheet (6). One has to replace doubly connected oxygen atoms by quadruply connected carbon atoms in order to preserve the electron count at Xe of Xe>.…”
Section: Electron Counting In the Antimony Substructuresmentioning
confidence: 99%
“…In order to check for any partial occupancies in the RAgSb2 series, which occur in the related RTSb2 phases with T = Mn, Fe, Co, Ni, Cu, Zn, and Cd (Sologub, 1994;Wollesen, 1996;Leithe-Jasper, 1994;Albering, 1996;Cordier, 1985), a single crystal structure determination was performed on GdAgSbz using a Rigaku AFC6R diffractometer with graphite monochromated Mo Ku (1.= 0.71069~) radiation and a 12 kW rotating anode generator. The data were collected at room temperature using the co-2e scan technique to a maximum 26 value of 60.2°.…”
Section: Single Crystal X-ray Diffractionmentioning
confidence: 99%